Studies In Kedah-Kelantan, Brahman And Crossbred Bulls At Puberty And Sexual Maturity - Dikiyati Yansumayutipa, Ismaya (1987)
Physiological differences within and between breeds could be important in genetic selection and in the planning of management programmes for maximization of reproductive efficiency. Data for this study were obtained from 21 Kedah-Kelantan bulls (6 to 36 months of age) maintained at Universiti Pertanian Malaysia. Data were also obtained from 109 Kedah- Kelantan bulls and 105 Brahman bulls (6 to 72 months of age) and 25 crossbred bulls (13 to 36 months of age) maintained at Darabif Sdn. Berhad. Heart girth, body weight, scrotal (ircumference, testes volume , testis length and testis width in all three breed s were measured. Semen production and plasma testosterone concentration were also investigated in Kedah-Kelantan bulls. Relationship between age, body size and testis size were found to be significantly different for all three breeds. Brahman bulls were superior to Kedah-Kelantan bulls with crossbred bulls in between. In all three breeds, heart girth increased rapidly between 14 and 21 months of age, besides body weight, scrotal circumference, testes volume, testis length and testis width. At 6 to 12, 13 to 18 and 19 to 24 months of age, 0 per cent, 26. 7 per cent and 83.3 per cent of Kedah-Kelantan bulls responded to electroejaculation, respectively. Whereas at over 30 months of age all Kedah-Kelantan bulls responded to electroejaculation.Semen quality was observed to increase with age.